Categorizing and Rating Patient Complaints: An Innovative Approach to Improve Patient Experience. (28th February 2021) - Bayer, Stephanie; Kuzmickas, Paul; Boissy, Adrienne; Rose, Susannah L.; Mercer, Mary Beth
The Ombudsman Office at a large academic medical center created a standardized approach to manage and measure unsolicited patient complaints, including methods to identify longitudinal improvements, accounting for volume variances, as well as incident severity to prioritize response needs. Data on patient complaints and grievances are collected and categorized by type of issue, unit location, severity, and individual employee involved. In addition to granular data, results are collated into meaningful monthly leadership reports to identify opportunities for improvement. An overall benchmark for improvement is also applied based on the number of complaints and grievances received for every 1000 patient encounters. Results are utilized in conjunction with satisfaction survey results to drive patient experience strategies. By applying benchmarks to patient grievances, targets can be created based on historical performance. The utilization of grievance and complaint benchmarking helps prioritize resources to improve patient experiences.